2015
DOI: 10.3341/kjo.2015.29.4.249
|View full text |Cite
|
Sign up to set email alerts
|

A Family with Axenfeld-Rieger Syndrome: Report of the Clinical and Genetic Findings

Abstract: PurposeTo describe clinical findings in a Korean family with Axenfeld-Rieger syndrome.MethodsA retrospective review of clinical data about patients with diagnosed Axenfeld-Rieger syndrome. Five affected members of the family underwent a complete ophthalmologic examination. We screened the forkhead box C1 gene and the pituitary homeobox 2 gene in patients. Peripheral blood leukocytes and buccal mucosal epithelial cells were obtained from seven members of a family with Axenfeld-Rieger syndrome. DNA was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The proband showed iris hypoplasia, corectopia, and peripheral anterior synechia; subject III-1 showed corectopia and peripheral anterior synechia in the right eye and iris hypoplasia, corectopia, polycoria, and peripheral anterior synechia in the left eye, even subject III-3 showed no abnormities. This is consistent with previous reports [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…The proband showed iris hypoplasia, corectopia, and peripheral anterior synechia; subject III-1 showed corectopia and peripheral anterior synechia in the right eye and iris hypoplasia, corectopia, polycoria, and peripheral anterior synechia in the left eye, even subject III-3 showed no abnormities. This is consistent with previous reports [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…Depending on the timing it manifests, high intraocular pressure will cause bulbar growth, corneal opacity owing to folds in Descemet's membrane (Haab's striae), and/or optic nerve and visual field damage. Secondary childhood glaucoma may also be present at birth or manifest into young adulthood; it goes hand in hand with morphological changes-such as aniridia, Axenfeld-Rieger syndrome (dysgenetic changes in the anterior chamber angle [6]), or Sturge-Weber syndrome (1).…”
mentioning
confidence: 99%
“…The authors detected a novel heterozygous mutation in the FOXC1 gene of the affected family members. Yang et al reported 5 ARS cases, in a three-generation family, with only ocular manifestations [ 12 ]. The authors detected two novel FOXC1 mutations, and suggested that ocular abnormalities (such posterior embryotoxon, iridocorneal adhesion, iris hypoplasia, or corectopia) and systemic abnormalities are frequently and occasionally, respectively, reported in ARS cases resulting from FOXC1 mutations; whereas, PITX2 mutations mainly cause polycoria and systemic abnormalities along with ocular defects.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic test was carried out at the GENESIS Medical Genetics Center in Poland. Genomic DNA was extracted from the patient’s blood sample following standard procedures (DNA miniprep kit for blood – Axygen Scientific, Union City, CA, USA) as described elsewhere [ 12 ]. Expending genomic DNA from the obtained specimen, the coding regions and splice junctions of the supposed gene were PCR amplified and capillary sequencing is performed (the technique of genetic testing PITX2 gene was Sanger sequencing of the coding exonic and flanking intronic regions of the respective genes.)…”
Section: Case Presentationmentioning
confidence: 99%